Proceedings of the 6th International Conference on Communities and Technologies 2013
DOI: 10.1145/2482991.2482998
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dynamics of ownership in community-oriented design projects

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Previous research in HCI has indicated that handing over responsibility can lead to an increased sense of ownership [51]. In our study we found that certain actors within the Trust took a strong sense of ownership over not only their consultation but also the research study.…”
Section: Taking Ownership and Giving Controlsupporting
confidence: 50%
“…Previous research in HCI has indicated that handing over responsibility can lead to an increased sense of ownership [51]. In our study we found that certain actors within the Trust took a strong sense of ownership over not only their consultation but also the research study.…”
Section: Taking Ownership and Giving Controlsupporting
confidence: 50%
“…We, furthermore, have to consider whether coming into a community with the agenda of completing research can ever fully be an exchange. There is always a foundational act of initiation, from a designer, a government agency or a community, that sets the project in motion (Light et al, 2013). When the ambition is research as well as designing, there is always the question of who benefits from the additional knowledge that comes from the engagement.…”
Section: Benefit For Whommentioning
confidence: 99%
“…But there continues to be a story to tell the advocates of collaborative work to demonstrate that designers are sometimes an adjunct to history, not its moving force; that groups of people worldwide can, and sometimes do, make their own futures. Sometimes they enlist a professional to help (Light et al, 2013). But, many times, they act, life changes and no one in the design world is much the wiser .…”
Section: Autonomíamentioning
confidence: 99%
“…But, many times, they act, life changes and no one in the design world is much the wiser . We need to tell this story because there is still a prevalent belief, despite extraordinary initiatives like the Transition Towns Movement (e.g., see Macy, 2007), that things start exogenously with someone who has training, status, authority or another form of design-power (Light et al, 2013). Even in the field of Participatory Design, which used to lead design practice in having political vision, the separation between designers and lay experts in the literature speaks to an Othering of lay partners -the very concept of participation presupposes there is something going on beyond you to which you can be invited (Light, forthcoming).…”
Section: Autonomíamentioning
confidence: 99%